SULAIMAN AL-QANUNI: SULTAN TERBESAR KERAJAAN TURKI USMANI - Dwi Ratnasari (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Sultan Sulaiman I is the greatest Muslim statesman of his time. The title